Hubungan Tingkat Pengetahuan Penjual terhadap Penggunaan Pengawet Natrium Benzoate pada Es Teh Jumbo di Kelurahan Kedungmundu dan Sendangmulyo Kota Semarang - Muslimah Muslimah; Hisyam Ammar Yanuardi; Chamim Faizin (Jurnal Kesehatan Amanah, 2026)
Indonesia faces various metabolic health problems that are often associated with food and beverage consumption, including chronic kidney disease. One contributing factor is the excessive use of food preservatives such as sodium benzoate, which may cause gastrointestinal disturbances, oxidative stress, inflammation, chronic kidney failure, and carcinogenic effects. This study aimed to determine the relationship between sellers’ knowledge level and the use of sodium benzoate preservative in jumbo iced tea sold in Kedungmundu and Sendangmulyo Subdistricts, Semarang City. The study employed an analytic quantitative method with a cross-sectional design. A total of 40 jumbo iced tea sellers were selected using simple random sampling. Sodium benzoate testing was conducted using UV-Visible spectrophotometry, and data were analyzed using Spearman’s rho correlation test. The results showed that 70% of respondents had a high level of knowledge, while 5% of samples were positive for sodium benzoate. Statistical analysis revealed a significant inverse relationship between sellers’ knowledge level and the use of sodium benzoate (p = 0.011; r = -0.397). This indicates that higher knowledge levels are associated with a lower likelihood of sodium benzoate use. In conclusion, there is a significant negative correlation between sellers’ knowledge and the use of sodium benzoate in jumbo iced tea.